A Comparative Assessment of Fracture Resistance of Zirconia Crowns Prepared With Different Finish Line Designs – A In Vitro Study - Jobin Joy; K Abhinav Mohan; Unni Pympallil; Cimmy Augustine; Lino Paul; Nirosha Vijayan (Journal of Pharmacy and Bioallied Sciences)
Introduction: The purpose of this work is to evaluate and contrast many finish line designs on monolithic zirconia crown fracture resistance. Materials and Methods: Four typhodont mandibular first molar teeth (Nissin TM) were acquired. Tooth preparation was performed. Teeth were classified into four categories according to the architecture of their margins. Group A: Flat-ended shoulder; Group B: Round-ended shoulder; Group C: Radial shoulder; Group D: Deep chamfer. Forty monolithic zirconia crowns were fabricated. One load-to---failure examination using a computer-operated universal testing machine assessed the zirconia crowns’ fracture strength. Results: The mean Fracture Resistance for Group A was 1254.266 ± 79.626, Group B was 2324.585 ± 113.996, Group C was 1461.733 ± 93.715, and Group D was 2768.063 ± 96.855. The difference in average Fracture Resistance among the four groups was statistically significant at P < 0.001. Conclusion: The outcomes of the current study reveal that the group with a deep chamfer finish line had the greatest fracture resistance. The group utilizing a flat-end shoulder finish line exhibited the lowest fracture resistance.